Is a Single Low Dose of Intrathecal Morphine a Useful Adjunct to Patient-Controlled Analgesia for Postoperative Pain Control Following Lumbar Spine Surgery? A Preliminary Report. (2015) - Yen, David; Turner, Kim; Mark, David
Abstract : BACKGROUND: Several studies addressing intrathecal morphine (ITM) use following spine surgery have been published either involving the pediatric population, using mid- to high-dose ITM, or not in conjunction with morphine patient-controlled analgesia (PCA). OBJECTIVES: To determine whether low-dose ITM is a useful adjunct to PCA for postoperative pain control following elective lumbar spine surgery in adults. METHODS: Thirty-two patients were enrolled in a double-blinded randomized controlled trial, and received either ITM or intrathecal placebo. Postoperatively, all patients were given a PCA pump and observed for the first 24 h in a step-down unit. Measurements of: total PCA morphine consumed in the first 24 h; intensity of pain; pruritus; nausea at 4 h, 8 h and 24 h; time to first ambulation; length of hospital stay; and occurrences of respiratory depression were recorded. RESULTS: The total PCA use was significantly lower in the ITM group. There were lower average pain scores in the ITM group, which increased to that of the intrathecal placebo group over 24 h; however, this failed to attain statistical significance. There were no differences in nausea, pruritus, time to first ambulation or hospital length stay. There were no cases of respiratory depression in either group. CONCLUSIONS: ITM may be a useful adjunct to PCA, but did not decrease time to ambulation or length of stay.